Flow diversion for the treatment of posterior inferior cerebellar artery aneurysms: a novel classification and strategies. (20th October 2017) - Srinivasan, Visish M; Ghali, Michael George Zaki; Reznik, Oleg E; Cherian, Jacob; Mokin, Maxim; Dumont, Travis M; Gaughen, John R; Grandhi, Ramesh; Puri, Ajit S; Chen, Stephen R; Johnson, Jeremiah N; Kan, Peter
Abstract : Background: The pipeline embolization device (PED) is frequently used in the treatment of anterior circulation aneurysms, especially around the carotid siphon, with generally excellent results. However, treatment of posterior inferior cerebellar artery (PICA) aneurysms with flow diversion (FD) has not been specifically described or discussed. While there are reports of treating PICA aneurysms using placement of FD stents in the vertebral artery, there are no reports of treating these lesions by placement of flow diverting stents in the PICA vessel itself. Due to the unique anatomy and morphology of these aneurysms, it requires special attention. We assessed our multi-institutional experience treating these lesions, including the first reported cases of the PED placed within the PICA. Methods: Institutional databases of neuroendovascular procedures were reviewed for cases of intracranial aneurysms treated with the PED. Patient and aneurysm data as well as angiographic imaging were reviewed for all cases of PICA aneurysms treated with the PED. PICA aneurysms were defined as aneurysms that involved the PICA. Vertebral aneurysms without disease in the PICA were excluded from the study. Results: 10 PICA aneurysms were treated during the study period. These were classified based on their morphology and location into two main types and five total subtypes for consideration of treatment with flow diversion. All aneurysms were successfully treated, with 8/10 completely obliterated and 2 with a partial reduction in size. Three patients had the PED placed entirely in the PICA and no patient suffered from a medullary or cerebellar stroke. All PEDs were patent and all patients were independent at the last follow-up. Conclusions: The PED may be used successfully to treat select aneurysms of the PICA. We present the first described cases of successful PED treatment of PICA aneurysms with direct placement of the PED in the PICA vessel itself. The proposed classification system aids in that selection.